2011
DOI: 10.1136/injuryprev-2011-040134
|View full text |Cite
|
Sign up to set email alerts
|

Building capacity of drivers in Nigeria to provide first aid for road crash victims

Abstract: This paper presents the effect of first aid training on the first aid knowledge and skills of university drivers. The intervention group (n=98) received training on first aid and controls (n=78) received training on HIV/AIDS. First aid knowledge and skills were measured at baseline, immediately after the training and 4 months post-intervention. Changes in knowledge and skills were assessed using repeated measures analysis of variance. Knowledge scores were 51.2±14.8%, 59.6±12.8% and 57.6±12.8% (p>0.05) for int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Thirteen studies reported the effect on first-aid skills6 12 16 21 22 27 29–35, and eleven demonstrated significantly greater first-aid skills in the intervention group than the control group during the post-training periods 6 12 16 21 22 27 29–33. Five of the seven studies that recruited only children or young peopled demonstrated significantly greater first-aid skills6 16 21 22 29 in the intervention group than the control group during the post-training periods, and the remaining two studies did not report the significance of the improvements in first-aid skills seen 34 35.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported the effect on first-aid skills6 12 16 21 22 27 29–35, and eleven demonstrated significantly greater first-aid skills in the intervention group than the control group during the post-training periods 6 12 16 21 22 27 29–33. Five of the seven studies that recruited only children or young peopled demonstrated significantly greater first-aid skills6 16 21 22 29 in the intervention group than the control group during the post-training periods, and the remaining two studies did not report the significance of the improvements in first-aid skills seen 34 35.…”
Section: Resultsmentioning
confidence: 99%
“…First aid training, for instance, contributes to UN Pillar 5 improving post-crash response. A study in Nigeria found that equipping drivers with first aid knowledge resulted in practical application when presented with a road crash victim (Sangowawa & Owoaje, 2012). This skill is critical in developing countries like South Africa, since emergency medical services are often limited in the country and may not be able to provide critical care that is required within the 'golden hour' after an injury (Vanderschuren and McKune, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Despite A few have gone a step further and investigated the effect of training lay firstresponders to form the first part of the prehospital trauma care system as an intervention (Sangowawa & Owoaje, 2012).…”
Section: Prehospital Trauma Care Systems In Low and Middle Income Coumentioning
confidence: 99%